Analysis of Muhammad Shahrur's thoughts on the concept of justice in polygamy: a perspective of contemporary Islamic law - Ulfa, Marliana; Abu Bakar, Norhayati; Faizal Abd Rahman, Muhammad (AL-MUQARANAH, 2024)
Polygamy, the practice of marrying more than one partner simultaneously, has been a controversial topic in Islamic law and modern society. Although it is permitted in the Qur'an (QS. An-Nisa` 3) on the condition of justice, its practical implementation is often debated, especially in relation to the principles of justice established. In this context, Muhammad Syahrur provides an innovative view on polygamy. He uses a linguistic and contextual hermeneutic approach to interpret Qur'anic verses, arguing that justice in polygamy includes not only equal distribution of material goods but also emotional and psychological well-being. Shahrur argues that the application of polygamy must take into account the social context and changing times, emphasizing that monogamy may be more appropriate for achieving justice in modern societies. The critique of traditional interpretations and the emphasis on the unattainable principle of absolute justice are the main focus of his methodology. The analysis suggests that although polygamy is permitted, practical justice may be more easily achieved through monogamy in the contemporary context, in accordance with the principles of human rights and gender equality.